Left atrial strain predicts incident atrial fibrillation in the general population: the Copenhagen City Heart Study. (11th October 2021) - Hauser, Raphael; Nielsen, Anne Bjerg; Skaarup, Kristoffer Grundtvig; Lassen, Mats Christian Højbjerg; Duus, Lisa Steen; Johansen, Niklas Dyrby; Sengeløv, Morten; Marott, Jacob Louis; Jensen, Gorm; Schnohr, Peter; Søgaard, Peter; Møgelvang, Rasmus; et al.
Abstract: Background: Left atrial (LA) strain parameters have been demonstrated to be valuable predictors of atrial fibrillation (AF) in several patient cohorts. The purpose of this study was to investigate whether LA strain, assessed by two-dimensional speckle-tracking echocardiography, can be used to predict the development of AF in the general population. Methods and results: This prospective longitudinal study included 4466 participants from the fifth Copenhagen City Heart Study. All participants underwent a health examination, including echocardiographic measurements of LA strain. Participants with prevalent AF at baseline were excluded. The primary endpoint was incident AF. During a median follow-up period of 5.3 years, 154 (4.3%) participants developed AF. In univariable analysis, peak atrial longitudinal strain (PALS), peak atrial contraction strain (PACS), and LA strain during the conduit phase were significantly associated with the development of AF. PALS [hazard ratio (HR) 1.05, 95% confidence interval (CI) (1.03–1.07), P < 0.001, per 1% decrease] and PACS (HR 1.08, 95% CI (1.05–1.12), P < 0.001, per 1% decrease] remained independent predictors of AF in multivariable analysis. In addition, PALS and PACS remained significantly associated with AF development even in participants with normal-sized atria and normal left ventricular (LV) systolic function. Conclusion: In the general population, PALS and PACS independently predict incident AF. These findings remained consistent even in participants with normal-sized LA and normal LV systolic function. Graphical Abstract: